Is it possible to predict low‐volume and insignificant prostate cancer by core needle biopsies?. Issue 4 (23rd August 2012) - Berg, Kasper Drimer; Toft, Birgitte Grønkaer; Røder, Martin Andreas; Brasso, Klaus; Vainer, Ben; Iversen, Peter
Abstract : In an attempt to minimize overtreatment of localized prostate cancer (PCa) active surveillance (AS) and minor invasive procedures have received increased attention. We investigated the accuracy of pre‐operative findings in defining insignificant disease and distinguishing between unilateral/unifocal and bilateral/multifocal PCa. One‐hundred and sixty patients undergoing radical prostatectomy were included. Histology reports from the biopsies and matching prostatectomies were compared. Three definitions of insignificant cancer were used: InsigE: tumour volume ≤0.5 mL; InsigW: tumour volume ≤1.3 mL; InsigM: tumour ≤5% of total prostate volume and prostate‐specific antigen (PSA) ≤10 ng/mL. In all definitions, Gleason score (GS) was ≤6 and the tumour was organ confined. Biopsies alone performed poorly as a predictor of unifocal and unilateral cancer in the prostatectomy specimens with positive predictive values of 17.8% and 18.9% respectively. Inclusion of other clinical and biochemical parameters did not significantly increase the predictive value. However, the combination of GS ≤ 6, PSA ≤ 10 ng/mL and unifocal or unilateral cancer in biopsy cores resulted in a positive predictive value of 61.1%, 38.9% and 12.0%, respectively, for identifying InsigM, InsigW and InsigE in the prostate specimen. Conclusively, routine prostate biopsies cannot predict unifocal and unilateral PCa, and must be regarded insufficient to select patients for focal therapy. Although candidates for AS may be identified using standard biopsies, a considerable fraction of patients will be understaged. There is a need for more precise diagnostic tools to assess intraprostatic tumour growth.